Effect of transplant center volume on post-transplant survival in patients listed for simultaneous liver and kidney transplantation - Modi, Rohan M (World J Hepatol, 2018)
AIM: To examine the effect of center size on survival differences between simultaneous liver kidney transplantation (SLKT) and liver transplantation alone (LTA) in SLKT-listed patients. METHODS: The United Network of Organ Sharing database was queried for patients ≥ 18 years of age listed for SLKT between February 2002 and December 2015. Post-transplant survival was evaluated using stratified Cox regression with interaction between transplant type (LTA vs SLKT) and center volume. RESULTS: During the study period, 393 of 4580 patients (9%) listed for SLKT underwent a LTA. Overall mortality was higher among LTA recipients (180/393, 46%) than SLKT recipients (1107/4187, 26%). The Cox model predicted a significant survival disadvantage for patients receiving LTA vs SLKT [hazard ratio, hazard ratio (HR) = 2.85; 95%CI: 2.21, 3.66; P < 0.001] in centers performing 30 SLKT over the study period. This disadvantage was modestly attenuated as center SLKT volume increased, with a 3% reduction (HR = 0.97; 95%CI: 0.95, 0.99; P = 0.010) for every 10 SLKs performed. CONCLUSION: In conclusion, LTA is associated with increased mortality among patients listed for SLKT. This difference is modestly attenuated at more experienced centers and may explain inconsistencies between smaller-center and larger registry-wide studies comparing SLKT and LTA outcomes.